FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TUBERCULOSIS DI KABUPATEN NAGAN RAYA - T.M. Rafsanjani T.M. Rafsanjani; Said Usman; Burhanuddin Syam; Irwan Saputra (Prosiding Seminar Nasional USM, 2019)
Indonesia 3rd ranks highest of Tuberculosis case in the world. There are 69 cases of Tuberculosis around Nagan Raya Regency, it is caused by many factors therefore need to know the problems that cause in The Regency. This research need to know connection Age, Gender, Education, Job, Knowledge and Socioeconomic effects Tuberculosis occurences. Population in this research were cases of Tuberculosis recorded in the health department of Nagan Raya number of 69 patients, they are taken from society of Nagan Raya regency by matching methode. The types of this research is Descriptive Analytic by approach to comparative cases (control) with a wiew Free Variable, they are Age, Gender, Education, Job, Knowledge, socioenomic and view Unfree Variable is patients of Tuberculosis with kuisoner division methode. The result of bivariat research shows : Age P=1.000, OR=1.226 (CI: 0511-1.956). Gender P=1.000, OR=2.000 (CI: 0.493-2.030). Education P=1.000, OR=1.156 (CI: 0.512-1.953).  Job P=0.016, OR= 1.571 (CI: 1.242-5.007). Knowledge  P=0.027, OR=1.024 (CI: 1.088-4.248). and Socio Economi P=0.026, OR=1.129 (CI: 0.221-0.866). There was no relationship and increased risk between Age with the incidence of Tuberculosis. There was no relationship and increased risk between Gender with the incidence of Tuberculosis. There was no relationship and increased risk between Education with the incidence of Tuberculosis. There was relationship and increased risk between Job with the incidence of Tuberculosis. There was relationship and increased risk between Knowledge with the incidence of Tuberculosis. There was relationship and increased risk between Socioeconomic with the incidence of Tuberculosis. Nagan Raya district health  office should improve the discovery suspected Tuberculosis, conduct outreach to increase Nagan Raya public awareness of Tuberculosis.